Analysis of Student Learning Motivation from a Holistic Perspective at Nurul Islam Islamic Senior High School - Siti Jamilah; Audy Pramudita; Nur Indah Yanuar Puspita; Maulid Agustin (Kasyafa: Jurnal Pendidikan Agama Islam, 2026)
Learning motivation is a crucial factor in educational success, particularly in Islamic education, which emphasizes a balance between academic achievement and the development of spiritual and moral character. This study aims to analyze students’ learning motivation from a holistic perspective at Madrasah Aliyah Nurul Islam by examining the interconnection of academic, spiritual, emotional, and social aspects. This research employs a case study method with a qualitative descriptive approach. Data were collected through observation, interviews with teachers and students, and documentation of learning and religious activities at the madrasah. The findings indicate that students’ learning motivation is influenced by a combination of internal and external factors. Internal factors include learning interest, self-confidence, academic goals, emotional stability, and spiritual awareness. External factors encompass teachers’ roles, parental support, classroom climate, the madrasah’s religious culture, and peer influence. The implementation of a holistic approach integrating religious practices, teacher mentoring, and collaborative learning has been shown to enhance students’ intrinsic motivation, learning engagement, and academic as well as moral responsibility. This study concludes that a holistic educational approach plays a strategic role in enhancing students’ learning motivation in madrasah settings. This approach not only improves academic achievement but also contributes significantly to the development of students’ character and spiritual growth in a comprehensive manner.